Bio-fabrication of zinc oxide nanoparticles from Brassica juncea (L.) Czern extract: Biological activity and DNA binding capability - S. Jeyaraj; A. Mary Saral (Results in Chemistry)
Recent years have seen a great deal of interest in the exceptional biological activities such as antioxidant, antimicrobial, antiinflammation, antidiabetic and anticancer activity of various biosynthesized Metal Oxide nanoparticles. Among these metal oxide nanoparticle ZnO NPs is gaining its important in various biological applications is increasingly gain prominence. Thus, the green production of ZnO NPs using plant extract has been demonstrated as a one step, environmentally friendly and cost-effective process. This paper describes the utilization of an aqueous extract of Brassica juncea (L.) Czern seed as a reducing agent in the creation of ZnO NPs from Zinc Sulfate using a green synthesis approach. UV–visible spectroscopic peak at around 363 nm verifies the production of ZnO NPs. FE-SEM was confirmed the spherical forms of produced ZnO NPs. The average particle size of produced ZnO NPs was found to be 13.35 nm from TEM analysis. On screening the ZnO NPs for antioxidant activity it showed scavenging activity with 62.40 %, with IC50 value of 68.30 µg/mL through DPPH assay. The antidiabetic activity was found to be 72 %, with IC50 value of 71.76 μg/mL, using alpha amylase assay. In anti-inflammatory activity, the activity was recorded as 68.50 % and IC50 value as 64.67 µg/mL, using BSA denaturation assay. The synthesized nanoparticles exhibited anticancer activity against the MCF-7 and A549 cell lines. The determined IC50 value of produced ZnO NPs for these two cell lines was found to be 43.83 µg/mL and 41.48 µg/mL respectively. Additionally, a hyperchromic shift in the absorbance was noted when CT-DNA interacted with biosynthesized ZnO NPs. These findings confirm that the ZnO NPs synthesized from Brassica juncea (L.) Czern seed exhibit significant biological properties namely antioxidant, antidiabetic and cytotoxic activity. Among all these activities, the biosynthesized ZnO NPs showed excellent cytotoxic activity with the IC50 values, thus proving its effectiveness.